Experimental Validation of Elliptical Fin-Opening Behavior - James M. Garner; Paul Weinacht; Robert P. Kaste (Shock and Vibration)
An effort to improve the performance of ordnance has led to the consideration of the use of folding elliptical fins for projectile stabilization. A second order differential equation was used to model elliptical fin deployment history and accounts for: deployment with respect to the geometric properties of the fin, the variation in fin aerodynamics during deployment, the initial yaw effect on fin opening, and the variation in deployment speed based on changes in projectile spin. This model supports tests conducted at the Transonic Experimental Facility, Aberdeen Proving Ground examining the opening behavior of these uniquely shaped fins. The fins use the centrifugal force from the projectile spin to deploy. During the deployment, the fin aerodynamic forces vary with angle-of-attack changes to the free stream. Model results indicate that projectile spin dominates the initial opening rates and aerodynamics dominate near the fully open state. The model results are examined to explain the observed behaviors, and suggest improvements for later designs.